Fabrication of Z-scheme photocatalyst, Er3+:Y3Al5O12@NiGa2O4-MWCNTs-WO3, and visible-light photocatalytic activity for degradation of organic pollutant with simultaneous hydrogen evolution. (August 2019) - Tang, Liang; Wang, Jing; Liu, Xudong; Shu, Xiaoqing; Zhang, Zhaohong; Wang, Jun
Abstract: Three new visible-light-induced Z-scheme photocatalytic systems, Er 3+ :Y3 Al5 O12 @NiGa2 O4 -WO3, Er 3+ :Y3 Al5 O12 @NiGa2 O4 -MWCNTs (10–20 nm)-WO3 and Er 3+ :Y3 Al5 O12 @NiGa2 O4 -MWCNTs (40–60 nm)-WO3, are successfully prepared via hydrothermal method. The prepared photocatalysts are characterized by X-ray diffractometer (XRD), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier-transform infrared (FT-IR) and photoluminescence (PL) spectra. UV–vis absorption and PL spectra were also determined to explore luminescence effect of the Er 3+ :Y3 Al5 O12 . The photocatalytic activities of prepared photocatalysts are evaluated and compared under simulated solar-light irradiation in degradation of organic pollutant with simultaneous hydrogen evolution. The influence factors such as simulated solar-light irradiation time and photocatalyst amount on the photocatalytic activities of prepared photocatalysts are investigated. The results show that the Er 3+ :Y3 Al5 O12 @NiGa2 O4 -MWCNTs (40–60 nm)-WO3 is the best one of three prepared photocatalysts in the degradation of methylene blue with simultaneous hydrogen evolution under simulated solar-light irradiation. In addition, the Er 3+ :Y3 Al5 O12 @NiGa2 O4 -MWCNTs (40–60 nm)-WO3 also displays high performance in five repeated experiments. At last, the process of photocatalytic degradation of organic pollutant with simultaneous hydrogen evolution caused by Er 3+ :Y3 Al5 O12 @NiGa2 O4 -MWCNTs (40–60 nm)-WO3 is proposed. Graphical abstract: Image 1